Foundations of chaplaincy : a practical guide - Baker, Alan T., 1956- (Michigan : William B. Eerdmans Publishing Company, 2021)
"A comprehensive introduction, overview, and reference book for the ministry of chaplaincy"--
Includes bibliographical references (pages 249-260) and index.
Keywords: Pastoral care; Chaplains